A evasão dos cursos de licenciatura em Geografia das universidades estaduais do Paraná (2010-2018) - Wilhelm, Marilene Francieli (2023)
This thesis is the result of a research carried out in the Graduation Program in Geography at Universidade Estadual do Oeste do Paraná (Unioeste), in the Francisco Beltrão campus, following the research line of Education and Geography Teaching. Dropout in teaching degree courses is a complex issue that became a challenge for higher education institutions, demanding a multifactorial comprehension (personal, social, economic, cultural, and institutional aspects) based on studies that observe each course specificities. Thus, this paper aimed to analyze and understand the dropout of teaching courses in Geography from state universities in Paraná, Brazil: Universidade Estadual de Maringá (UEM), Universidade Estadual do Centro-Oeste (Unicentro), Universidade Estadual do Oeste do Paraná (Unioeste), Universidade Estadual de Ponta Grossa (UEPG), Universidade Estadual do Paraná (Unespar), and Universidade Estadual do Norte do Paraná (UENP). The following questions were raised to guide this investigation: What are the main factors that cause a dropout from the Geography teaching degree course in state higher education institutions from Paraná? How have such courses been contributing to prevent/decrease dropout? Do the affirmative action policies intervene in the students’ stay at college? The research, of a qualitative and quantitative nature, takes the form of case studies. The focus of the analysis was based on the perspective of dropout students, with a temporal focus from 2010 to 2018. The first stage consisted of a bibliographic survey, with consultation of official national and state documents on enrollments and dropouts. The subsequent stages were characterized by the assessment of the Human Research Ethics Committee (CEP)/Unioeste, an internal survey of the Higher Education Institutions (HEIs) researched (quantitative data related to entrants/graduates/dropouts/current students and qualitative data relating to identification and contacts (telephone, email) of research subjects/selected subjects). he subjects were then located through contact via telephone and social networks (Facebook/Messenger, Instagram, email and WhatsApp). From this perspective, through a semi-open interview/questionnaire, 556 dropouts from the State Universities of Paraná participated in the research. In addition to the subjects mentioned, dialogue took place with teachers who were and/or are coordinators of the respective courses, in order to verify the perception regarding evasion. With the data obtained, tables, graphs and figures were created that systematized the dropout scenario in Geography degree courses in the state of Paraná. In conjunction with the bibliographical survey, the information collected made it possible to develop the profile of evaders and identify factors that could reduce evasion. Based on the returns, in general, 62.9% of respondents cited individual factors for evasion. According to the order of importance, the factors were listed: 1st) difficulty in combining work burdens and tasks arising from studies at university; 2nd) personal difficulties of adaptation to university life, especially financial issues and 3rd) disenchantment/misinformation with the chosen undergraduate course and lack of interest in continuing at university, obtaining a place in the Geography/Bachelor's degree course was a result of second choice in the entrance exam.